Intra-operative Oxycodone Reduced Postoperative Catheter-Related Bladder Discomfort Undergoing Transurethral Resection Prostate. A Prospective, Double Blind Randomized Study - Xiong, Juncheng; Chen, Xiang; Weng, Chengwei; Liu, Shuqun; Li, Jian (Urology Journal, 2019)
Purpose: To observe the efficacy of intravenously injected oxycodone intraoperative on postoperative urinary catheter-related bladder discomfort (CRBD). Materials and Methods: Patients with ASA I-III received trans-urethral resection prostate under general anesthesia were observed. Patients were randomized allocated to the group control (n = 45) received placebo and the group oxycodone (n =46 ) received 0.03mg/kg of oxycodone before the end of operative 10min. The incidence and severity (mild, moderate, severe) of CRBD were assessed at 0, 1/2 h, 2 h and 6 h postoperatively. VAS scores were used to assess pain intensity during the same period. Postoperative PCA analgesic sufentanil dose and the incidences of nausea, vomiting, dizziness, over sedation were recorded in these patients. Results: Compared with the control group, the incidence of CRBD was significantly lower in the oxycodone group at 0 [22 (49 %) vs. 10 (22%); P = .007], 1/2h [18 (40%) vs. 9 (20%); P= .033], 2h [11 (24%) vs. 4 (9%); P = .001]. The severity of CRBD at 0 [mild, 9 (38%) ; moderate 9 (20%), severe 4 (9%)] was lower in the group Q than the controlled group [mild, 4 (38%) P ? .023; moderate 5 (11%), P ?.034, severe 1 (2%), P ? .012]. 1/2 h [mild, 11 (24%) Vs 5(11%), P ? .020]. Compared with the group C, VAS scores were lower in group Q at 0, 1/2h (P ? .001) and significantly decreased sufentanil dosage within 6h ( P= .001). There were no significant differences in the incidence of postoperative adverse effects between two groups. Conclusion: Oxycodone can effectively prevent patients with CRBD after TURP without incurring serious adverse effects.